Influence of past advanced behavior guidance experience on parental acceptance for autistic individuals in the dental setting - Apichaya Manopetchkasem; Natchalee Srimaneekarn; Pattarawadee Leelataweewud; Apiwan Smutkeeree (BMC, 2023)
Abstract Background Autism is a lifelong neurodevelopmental disorder that poses challenges during dental treatment. Advanced behavior guidance techniques (BGTs) have been used to provide dental care for autistic people who have specific characteristics and complex dental treatment. This study was conducted to evaluate parental acceptance and analyze parents' opinions of advanced BGTs during dental treatment in autistic people. Methods This cross-sectional study was conducted on 141 parents of autistic people from the Mahidol Dental Hospital and the Autism online community. Informed consent was obtained before enrolling participants in the study. All parents were asked to rate their acceptance after watching VDO clips: passive restraint by device (PRBD), oral sedation (OS), and general anesthesia (GA) to evaluate parental acceptance of advanced BGTs through an online questionnaire survey. The online questionnaire included a visual analog scale (VAS) and open-ended questions to collect their opinions on each advanced BGT. Participants were categorized into two subgroups as follows: 81 in the "Experience group" and 60 in the "No experience group" according to their autistic people' advanced BGT experience. Friedman's two-way analysis of variance and the Mann-Whitney U test were used for statistical analyses. Open-ended questions were analyzed using quantitative content analysis. Results PRBD was ranked the highest, followed by GA and OS. Parents in the "Experience group" rated significantly higher acceptance of their BGT experience than parents in the "No experience group" in all the three advanced BGTs. Conclusions All advanced BGTs were particularly accepted in this study. Previous experience of advanced BGTs had an influence on parental acceptance. Parents commented on their opinions toward each advanced BGT with a variety of perspectives. Trial registration: The protocol was approved by the ethical committee of the Faculty of Dentistry/Faculty of Pharmacy, Mahidol University (COA.No.MU-DT/PY-IRB 2021/022.1702) and was registered with Thai Clinical Trials Registry (TCTR20220521001).